CUSTO-EFETIVIDADE DE MÉTODOS DE IMPLANTAÇÃO DE BARU, Dipteryx alata Vogel (Fabaceae) SOB EFEITO DE FILTROS AMBIENTAIS - LUANDA CAROLINE PARREIRA DE PAULA (2021)
Improving the cost-effectiveness of planting actions for ecological restoration has been increasingly sought. However, the existence of environmental filters in areas undergoing restoration are obstacles to achieving this success, which may increase costs and reduce effectiveness. Moreover, restoration techniques via seedling planting and direct seeding have commonly been used in most implantations where active restoration is required. In the case of seedlings, the hydrogel polymer is used to improve the water establishment on site and at sowing, the good seed storage over time, since after harvest they are stored until the time of implantation, has been one of the main causes for the success of the field emergency. Given this reality, we have compared the effective cost of planting seedlings all with hydrogel and direct seeding with and without hydrogel, in two storage times, under the effect of different environmental filters (herbivory and water deficit compared to the absence of these filters) in Dipteryx alata Vogel, a species of economic interest from the Cerrado. To evaluate the performance of the two methods, we analyzed survival, relative growth rate (RGR) of height, diameter and crown area, as well as exposed ground cover and weed grasses compared by analysis of variance ANOVA. We performed germination tests conducted in laboratory in order to compare seeds stored after different periods. Our results demonstrate that in areas under higher degrees of environmental filters (herbivory and water deficit), both techniques do not achieve a high percentage of survival. However, when the degree of these filters is not clear and, survival is greater for both methods (seedlings and planting seedling), while, under the effect of herbivory, the type of the technique does not interfere to achieve a survival greater than 6% and under water deficit planting seedlings the survival rate is >50%. The use of hydrogel didn’t increase survival in general, and, therefore it’s use is not noticeable under these conditions (noting that the implantation was at the end of the dry season, that is, its use at the beginning of the rainy season still needs to be investigated). The germination of seeds with shorter storage time in the laboratory reached a percentage 50% higher than that of seeds with longer storage time, but in the field this difference in survival was not observed. Seedling growth was mainly influenced by environmental filters. Neither assessed filters nor treatments influenced grass invasion nor the presence of exposed soil. Due to the fact planted seedlings presented a significantly better results, when evaluating the best cost-effectiveness in general (and including those of the filters), they have better cost-effectiveness, being the most suitable arrangement. Compared to favourable conditions, herbivory is more than 20 times higher while water deficit triples the cost-effectiveness of restoration. This result is specifically relevant as it clearly demonstrates the forecast of the increase in restoration costs under future climate change scenarios, considering the forecast of a decrease in precipitation. We conclude that the assessed environmental conditions directly affected the cost-effectiveness of both methods of implementation to the D.alata specie, therefore, the environmental conditions must be considered in the planning in order to achieve national and global restoration goals.